2018
DOI: 10.24875/ric.18002516
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stents as Bridge to Surgery for Acute Left-Sided Obstructive Colorectal Cancer: Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The role of self-expanding metallic stents (SEMS) as a bridge to surgery for acute left-sided obstructive colorectal cancer has remained controversial. Objective: To study the efficacy of this approach, we performed a meta-analysis at the gastrointestinal surgery center of Sichuan Academy of Medical Sciences and Sichuan Provincial People's Hospital (Eastern Hospital). Methods: Two PubMed and science-direct electronic databases were searched up to December 30, 2017. Eligible studies were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…This metaanalysis highlighted that SEMS as BTS does not confer an advantage in short-term mortality [12] in contrast with previous meta-analyses [33À36]. The findings by Arezzo et al were recently confirmed by another 2 meta-analyses, respectively by Yang et al [37] and by Boland et al [38]. Colostomy is often maintained for life, due to comorbidities or willingness to avoid re-operation in elderly patients, carrying a significant deterioration in the quality of life.…”
Section: Comparison With Es: Short-term Outcomesmentioning
confidence: 80%
“…This metaanalysis highlighted that SEMS as BTS does not confer an advantage in short-term mortality [12] in contrast with previous meta-analyses [33À36]. The findings by Arezzo et al were recently confirmed by another 2 meta-analyses, respectively by Yang et al [37] and by Boland et al [38]. Colostomy is often maintained for life, due to comorbidities or willingness to avoid re-operation in elderly patients, carrying a significant deterioration in the quality of life.…”
Section: Comparison With Es: Short-term Outcomesmentioning
confidence: 80%
“…Finally, the issue related to stomas. We, unlike Allievi et al 5 and Yang et al, 4 considered temporary and permanent stoma rates separately, rather than global stoma rates, which could be confounding. Nevertheless, whether one considers the global incidence of stomas, or the temporary and permanent stoma rates, whether one uses the odds ratio or the risk ratio, an advantage in favor of stent bridge to surgery is always demonstrated.…”
Section: Responsementioning
confidence: 94%
“…Nevertheless, our systematic review and meta-analysis appeared in the literature earlier than the other 4 meta-analyses cited. [3][4][5][6] Therefore, I would not be surprised if the reviews published later, such as that by Yang et al, 4 report similar results and conclusions, and no new relevant information.…”
Section: Responsementioning
confidence: 97%
See 1 more Smart Citation
“…Most studies showed that the prognoses of patients with left-sided CRC were better than those of patients with right-sided CRC [5][6][7][8]. Intestinal obstruction is more likely to occur on the left-sided because the right-sided colon wall is thin and easy to expand [9][10][11]. The more abundant blood supply in the right-sided colon results in faster tumour growth, more prone to necrosis, bleeding, and secondary infection and leads to the more common clinical characteristics including anaemia, emaciation, fever, and dyscrasia [12,13].…”
Section: Introductionmentioning
confidence: 99%